Commercialized biomarkers: new horizons in prostate cancer diagnostics. (June 2015) - Murphy, Lisa; Prencipe, Maria; Gallagher, William M; Watson, R William
Abstract : Limitations with current clinical tools available for diagnosis and prognosis of prostate cancer (PCa) have resulted in overdiagnosis and costly overtreatment, which is affecting the outcomes and quality of life of men. The biotech industry is investing significant resources into developing more specific biomarkers for PCa detection and patient stratification that would greatly advance the decision-making processes behind PCa management and treatment. In this review, we focus on those biomarkers that have been translated into commercial tests available to clinicians. Since these tests aim to fill specific gaps during the decision-making process of PCa management, we have grouped them based on the clinical question they claim to address, that is, improved PCa screening, false-negative biopsy dilemma, prognostic tests following a positive biopsy and tests predicting relapse/metastases after surgery. We evaluate each test with respect to its development, platform, clinical validation, biomatrix, regulatory approval status and cost.